Professional Development on Digital Literacy and Transformative Teaching in a Low-Income Country : A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading Research Quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.